Celiac Disease and Skin Diseases: A Bidirectional Mendelian Randomization Study - Ge C; Wang Y; Zhao X; Hao J; Zhang J; Lu M; Li C; Feng J; Zhang Q (Clinical, Cosmetic and Investigational Dermatology)
Chenyang Ge,1 Yizheng Wang,2 Xuegang Zhao,1 Jiawen Hao,1 Jing Zhang,1 Mengyuan Lu,1 Congying Li,1 Jianke Feng,1 Qingfu Zhang1 1Burn and Wound Repair Center, Hebei Medical University Third Hospital, Shijiazhuang, Hebei, 050000, People’s Republic of China; 2Department of Pain and Rehabilitation, The Fourth Hospital of Hebei Medical University, Shijiazhuang, Hebei, 050000, People’s Republic of ChinaCorrespondence: Qingfu Zhang; Jianke Feng, Burn and Wound Repair Center, Hebei Medical University Third Hospital, No. 139 Ziqiang Road, Qiaoxi District, Shijiazhuang, Hebei Province, 050051, People’s Republic of China, Tel +86 18533112550 ; +86 18633889629, Email 16601225@hebmu.edu.cn; 37500444@hebmu.edu.cnBackground: Research as shown that celiac disease (CD) is associated with skin diseases, but their causality remains unclear. Therefore, this Mendelian randomization (MR) study evaluated the causality between CD and skin diseases.Methods: Bidirectional MR analysis was performed on single nucleotide polymorphism (SNP) candidates identified from genome-wide association study (GWAS) datasets using inverse variance weighted (IVW), weighted median, MR-egger, weighted mode and simple mode. Multivariate MR (MVMR) analysis was subsequently conducted by adjusting for BMI, smoking, and alcohol use. Result reliability was assessed by horizontal pleiotropy and heterogeneity testing.Results: IVW analysis revealed that CD increased the risk of atopic dermatitis (OR = 1.042, 95% CI: 1.018– 1.067, P = 5.75 × 10− 4) and cellulitis (OR = 1.026, 95% CI: 1.006– 1.046, P = 9.18× 10− 3). Additionally, psoriasis had a suggestive association with CD (OR=0.836, 95% CI: 0.710– 0.983, P = 0.031). MVMR analysis demonstrated that CD had a direct effect on atopic dermatitis and cellulitis.Conclusion: CD contributes to higher risks of atopic dermatitis and cellulitis. Additionally, psoriasis is suggestively associated with CD. Nonetheless, further research is warranted to confirm these findings and to elucidate the underlying mechanisms.Keywords: celiac disease, skin diseases, causality, Mendelian randomization